Forest goods and services in Uruguay: evaluation of the most important non timber forest products - Sans, C.; Daniluk, G.; López Quero, M. (Agrociencia Uruguay, 2007)
Uruguayan forestry sector has experienced an important increase in the forested area since the approval of the forestry law in 1987. More than 600 000 ha are covered by pine and eucaliptus forests to produce industrial timber (pulpwood, sawntimber, firewood). Other non wood materials or services provided by forests are not usually included in forest plans. This study is done under the scope of «multiple uses of forests» research program of the Forest Production and Wood Technology Department with the collaboration of the Polytechnic University of Madrid. The first study on this subject was done as a final under graduate thesis and continues as a case study for a private forest enterprise. Bibliographical reviews and documents of consultancies or punctual experiences on the different uses of the forests are another background. The main aim of this study is to gather non timber forests products in pine and eucaliptus forests to generate new alternatives for use in Uruguay. A survey in four enterprises of the four main forestry regions of the country was made as well as in coastal forests. Results show that all forestry enterprises use forests for silvopastoralism and it is quite profitable. Apiculture follows in importance, on the other hand products like fungi and cone are obtained by an informal way in the coastal forests but this does not happens in the other forests.